Special Issue: ‘Sustainable Viticulture: Soil Fertility, Plant Nutrition and Grape Quality’ - Fernando Visconti; Roberto López; Miguel Ángel Olego (Horticulturae, 2025)
Sustainable viticulture is the practice of growing grapes indefinitely—for winemaking, juice production, or fresh or dry consumption—while upholding the highest standards of product quality and environmental stewardship [...]